Breaking Barriers in Orthodontics: An Experimental Study on How Stabilization Discs Improve Mini-Implant Outcomes - Tinela Panaite; Cristian Liviu Romanec; Mihnea Iacob; Carina Balcos; Carmen Savin; Nicolae Daniel Olteanu; Raluca-Maria Vieriu; Chehab Alice; Irina Nicoleta Zetu (Dentistry Journal)
Background/Objectives: The stabilization disc (SD) for orthodontic mini-implants is a novel device designed to enhance anchorage stability and minimize the risk of mini-implant mobility. The disc features a flat structure with four prongs and is crafted from biocompatible materials such as titanium or stainless steel. It provides additional support to mini-implants by improving force distribution and reducing stress concentration around the insertion site. This study aims to evaluate the biomechanical performance of mini-implants with an SD compared to without-SD mini-implants, with a specific focus on their ability to maintain anchorage under orthodontic loading conditions. Methods: A finite element analysis (FEA) model was created for a commercially available mini-implant (2.0 mm in diameter and 12 mm in length). The mandible’s anatomical structure was reconstructed in 3D from computed tomography (CT) scans using SpaceClaim software 2023.1. To simulate real-world orthodontic conditions, forces of 10 N were applied at an angle of 30°. This retrospective study explores the role of SDs in enhancing mini-implant stability by reducing displacement and optimizing stress distribution. The evaluation included analyzing von Mises stress, cortical bone deformation, and mini-implant movement under simulated orthodontic loading. Results: The results demonstrate that the SD significantly reduces maximum total displacements by over 41% and redistributes von Mises stresses more evenly across the mini-implant and surrounding bone. Cortical bone stress and deformation were reduced in cases utilizing the SD, indicating enhanced implant stability and durability. Conclusions: The stabilization disc enhances mini-implant stability by improving stress distribution and reducing deformation without requiring permanent implant modifications. Its adaptability makes it a valuable solution for managing variable bone density and high orthodontic forces, offering a promising advancement in orthodontic anchorage.